The global First World War
1 online resource (xii, 234 pages)
Keywords: "This volume deals with the multiple impacts of the First World War on societies from South Europe, Latin America, Asia and Africa, usually largely overlooked by the historiography on the conflict. Due to the lesser intensity of their military involvement in the war (neutrals or latecomers), these countries or regions were considered "peripheral" as a topic of research. However, in the last two decades, the advances of global history recovered their importance as active wartime actors and that of their experiences. This book will reconstruct some experiences and representations of the war that these societies built during and after the conflict from the prism of mediators between the war fought in the battlefields and their homes, as well as the local appropriations and resignifications of their experiences and testimonies"--